COMMON SENTENCE ERRORS FOUND ON ONLINE DIARY OF 8TH BATCH SEA TEACHER BLOG WRITING - Muwafiqul Ihsani; Entika Fani Prastikawati; Faiza Hawa (Universitas Majalengka, 2020)
This study aimed to identify the common sentence errors that found on online diary of 8th batch SEA Teacher blog writing in University of Santo Tomas Philippines, to identify the most dominant errors found on online diary of 8th batch SEA teacher blog writing in University of Santo Tomas Philippines, to describe the problems faced by 8th batch SEA teacher in University of Santo Tomas Philippines in writing online diary. The research design of this study was descriptive qualitative. For collecting data, the writer used non-interactive techniques by analyzing nine online diaries and distributing questionnaire. Moreover, the writer employed three steps for analyzing the data, namely data reduction, data display, and drawing conclusion. The writer analyzed nine online diaries. The writer found the common sentence errors on nine online diaries written by 8th batch SEA teacher in University of Santo Tomas Philippines. The most dominant error was fragment (45%) followed by run-on sentence (31%), and dangling modifier (24%). Whereas, problems faced by 8th batch SEA teacher in University of Santo Tomas Philippines were the poor ability to arrange the good structure of writing, the lack of time management, the lack of experience in writing and designing or even using a blog and the lack of creativity to convert the diary into communicative one. Keywords: Common Sentence Errors, Fragment, Run-on Sentence, Dangling Modifier, Online Diary, Blog Writing